Isırgan tohumu lipazının enzimatik hidroliz yönteminde kullanılabilirliğinin incelenmesi - Tokman, Nilgün (Fen Bilimleri Enstitüsü, 1996)
The present industrial process for fat and oil hydrolysis involves pressures of ca. 50 atm and temperatures of 240-260 °C or higher for a period of ca. 2 hr to achieve 96-99% hydolysis. The resulting products are extremely dark fatty acids and discolored dilute (10%) aqueous solution of glycerol. The fatty acids are unusable as obtained and need to be redistilled to remove color and by-products. These processes are energy intensive and give rise to a variety of undesirable side reactions. In order to conserve energy and obtain light-colored fatty acids, investigators set out to study enzymatic hydrolysis of triglycerides. On the contrary, some factories in Japan already use lipase for production of soap powder and production of high purity unsaturated fatty acid. A variety of lipases of different origins have been studied in the biochemical literatures. Pancreatic lipase was the first fat-splitting enzyme to be thoroughly investigated. Each of the enzymes catalyze a different kind of chemical reaction. All enzymes are proteins with enourmous catalytic activity produced by living cells, the enzyme activity varying considerably to the source of the enzyme. They have very complex and specific three-dimensional conformation in which the chains are folded. This conformation is necessary for the activity of the enzyme. The enzymes, like other proteins, can undergo denaturation. When this occurs their activity is lost. The enzymes, known as lipases, function at the oil- water interface to hydrolyze fats to fatty acids and glycerol. The reaction catalyzed by enzyme proceeds as follows : E + S ^ ES ?=i E+P k2 E : Enzyme S : Substrate IX Samples were with drawn at predetermined time intervals and placed in a 90 °C water bath for 15 min to inactive the enzyme. Then, they were centrifuged to seperate the lipase, and the oil phase was dried using anhydrous Na^C^. At the same time, 0. 1 g hydrolyzed oil was added to 10 ml chloroform and analyzed by thin-layer chromatography-flame ionization detection (TLC-FID) analyser (Iatron laboratories Inc. Tokyo, Japan). Complete seperation of the lipid mixture was achieved into triglyceride (TG), fatty acid (FA), 1,3-diglyceride (1,3- DG), 1,2-diglyceride (1,2-DG), 2-monoglyceride (2-MG) and 1-monoglyceride (1- MG). For the investigation of potential application of Nettle seed lipase "acetone powder" in the enzyme-catalyzed hydrolysis, lipase "acetone powder" was prepared by charging blender, equipped with a 1000 ml glass container, with 100 g Nettle Seed, followed by 200 ml of acetone, then ground for 3-5 min. The resulting mixture was transferred into a 1000 ml beaker, which was cooled by salt-ice mixture and the glass container was rinsed with 150 ml of acetone. The acetone was added to the original mixture, the stirred for 1 min. The suspension containing low density material was carefully decanted into a Buchner funnel equipped for vacuum filtration. The seed residue was washed with two 250 ml portions of acetone. Acetone wash was added to the filter cake. The filter cake was transferred into a 1000 ml beaker which was cooled by salt-ice mixture, and then wash with two 150 ml portions of acetone, followed by another 100 ml portion. The combined acetone wash was vacuum filtered. The powder was transferred and spread on to an appropraitely sized filter paper, then air-dried under a hood. The powder was stored at 4°C until required. The acetone powder, prepared according to this method developed by Afolabi and co-workers, was used in hydrolysis reactions as catalyst. The degree of hydrolysis was calculated by the following equation: Hydrolysis % = 100 (AV2 - AV,) / (SV - AV,) where AV! and AV2 are acid value of samples at the initial time and time t, respectively and SV is the saponification value of used frying oil. In order to determine the effect of lipase content on enzymatic hydrolysis of used frying oil, four different amount of lipase have been tested. The results are shown in Table 1. As can be seen increasing the lipase content increased the rate of hydrolysis. XI SUMMARY THE HYDROLYSIS OF USED FRYING OIL BY NETTLE SEED LIPASE (URTICA PILULIFERA LIPASE) The present industrial process for fat and oil hydrolysis involves pressures of ca. 50 atm and temperatures of 240-260 °C or higher for a period of ca. 2 hr to achieve 96-99% hydolysis. The resulting products are extremely dark fatty acids and discolored dilute (10%) aqueous solution of glycerol. The fatty acids are unusable as obtained and need to be redistilled to remove color and by-products. These processes are energy intensive and give rise to a variety of undesirable side reactions. In order to conserve energy and obtain light-colored fatty acids, investigators set out to study enzymatic hydrolysis of triglycerides. On the contrary, some factories in Japan already use lipase for production of soap powder and production of high purity unsaturated fatty acid. A variety of lipases of different origins have been studied in the biochemical literatures. Pancreatic lipase was the first fat-splitting enzyme to be thoroughly investigated. Each of the enzymes catalyze a different kind of chemical reaction. All enzymes are proteins with enourmous catalytic activity produced by living cells, the enzyme activity varying considerably to the source of the enzyme. They have very complex and specific three-dimensional conformation in which the chains are folded. This conformation is necessary for the activity of the enzyme. The enzymes, like other proteins, can undergo denaturation. When this occurs their activity is lost. The enzymes, known as lipases, function at the oil- water interface to hydrolyze fats to fatty acids and glycerol. The reaction catalyzed by enzyme proceeds as follows : E + S ^ ES ?=i E+P k2 E : Enzyme S : Substrate IX Samples were with drawn at predetermined time intervals and placed in a 90 °C water bath for 15 min to inactive the enzyme. Then, they were centrifuged to seperate the lipase, and the oil phase was dried using anhydrous Na^C^. At the same time, 0. 1 g hydrolyzed oil was added to 10 ml chloroform and analyzed by thin-layer chromatography-flame ionization detection (TLC-FID) analyser (Iatron laboratories Inc. Tokyo, Japan). Complete seperation of the lipid mixture was achieved into triglyceride (TG), fatty acid (FA), 1,3-diglyceride (1,3- DG), 1,2-diglyceride (1,2-DG), 2-monoglyceride (2-MG) and 1-monoglyceride (1- MG). For the investigation of potential application of Nettle seed lipase "acetone powder" in the enzyme-catalyzed hydrolysis, lipase "acetone powder" was prepared by charging blender, equipped with a 1000 ml glass container, with 100 g Nettle Seed, followed by 200 ml of acetone, then ground for 3-5 min. The resulting mixture was transferred into a 1000 ml beaker, which was cooled by salt-ice mixture and the glass container was rinsed with 150 ml of acetone. The acetone was added to the original mixture, the stirred for 1 min. The suspension containing low density material was carefully decanted into a Buchner funnel equipped for vacuum filtration. The seed residue was washed with two 250 ml portions of acetone. Acetone wash was added to the filter cake. The filter cake was transferred into a 1000 ml beaker which was cooled by salt-ice mixture, and then wash with two 150 ml portions of acetone, followed by another 100 ml portion. The combined acetone wash was vacuum filtered. The powder was transferred and spread on to an appropraitely sized filter paper, then air-dried under a hood. The powder was stored at 4°C until required. The acetone powder, prepared according to this method developed by Afolabi and co-workers, was used in hydrolysis reactions as catalyst. The degree of hydrolysis was calculated by the following equation: Hydrolysis % = 100 (AV2 - AV,) / (SV - AV,) where AV! and AV2 are acid value of samples at the initial time and time t, respectively and SV is the saponification value of used frying oil. In order to determine the effect of lipase content on enzymatic hydrolysis of used frying oil, four different amount of lipase have been tested. The results are shown in Table 1. As can be seen increasing the lipase content increased the rate of hydrolysis. XI SUMMARY THE HYDROLYSIS OF USED FRYING OIL BY NETTLE SEED LIPASE (URTICA PILULIFERA LIPASE) The present industrial process for fat and oil hydrolysis involves pressures of ca. 50 atm and temperatures of 240-260 °C or higher for a period of ca. 2 hr to achieve 96-99% hydolysis. The resulting products are extremely dark fatty acids and discolored dilute (10%) aqueous solution of glycerol. The fatty acids are unusable as obtained and need to be redistilled to remove color and by-products. These processes are energy intensive and give rise to a variety of undesirable side reactions. In order to conserve energy and obtain light-colored fatty acids, investigators set out to study enzymatic hydrolysis of triglycerides. On the contrary, some factories in Japan already use lipase for production of soap powder and production of high purity unsaturated fatty acid. A variety of lipases of different origins have been studied in the biochemical literatures. Pancreatic lipase was the first fat-splitting enzyme to be thoroughly investigated. Each of the enzymes catalyze a different kind of chemical reaction. All enzymes are proteins with enourmous catalytic activity produced by living cells, the enzyme activity varying considerably to the source of the enzyme. They have very complex and specific three-dimensional conformation in which the chains are folded. This conformation is necessary for the activity of the enzyme. The enzymes, like other proteins, can undergo denaturation. When this occurs their activity is lost. The enzymes, known as lipases, function at the oil- water interface to hydrolyze fats to fatty acids and glycerol. The reaction catalyzed by enzyme proceeds as follows : E + S ^ ES ?=i E+P k2 E : Enzyme S : Substrate
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 1996
Keywords: Enzimatik yöntemler; Hidroliz; Isırgan otu; Lipaz; Enzymatic methods; Hydrolysis; Stinging nettles; Lipase